Kohesi dan Koherensi dalam Teks Sholawat Qobla Maulid Diba’: Analisis Semantik Wacana - Salsabila Nova Fatimah; Athian Sulthon; Ahmad Dardiri; Wati Susiawati (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to examine the forms of cohesion and coherence found in the text Sholawat Qobla Maulid Diba’ through a discourse-semantic perspective. The urgency of this research stems from the understanding that religious texts—particularly shalawat—do not merely function as spiritual expressions of praise and prayer to Prophet Muhammad (peace be upon him), but also manifest as complete linguistic constructions that are aesthetic, unified, and rich in meaning. In linguistics, the study of cohesion and coherence plays a crucial role in uncovering how form and meaning interact within discourse, thereby explaining how a text achieves unity, clarity, and communicative strength.This research adopts a qualitative descriptive method by analyzing the verses of the shalawat using the theoretical framework of grammatical cohesion (reference, substitution, ellipsis, conjunction, and parallelism) and lexical cohesion (repetition, synonymy, antonymy, collocation, and semantic field). The analysis also encompasses aspects of semantic coherence, such as causal, temporal, associative, and contrastive relations.The results reveal that Sholawat Qobla Maulid Diba’ contains a strong degree of grammatical cohesion, evident in its usage of pronouns, parallel structures, and connective conjunctions. Lexical cohesion is established through the repetition of devotional expressions, systematic collocations, and semantic contrasts that reinforce the text’s spiritual message. Furthermore, coherence is reflected in the orderly semantic progression throughout the discourse, forming a unified, harmonious, and meaningful whole. Consequently, this shalawat functions not only as a medium of spiritual devotion but also as a cohesive and coherent work of linguistic artistry.